(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The study of scientific work on research conducted in recent years shows us the need for scientific justification by identifying effective tools and methods that promote the improvement of the technical and tactical training of young taekwondo practitioners and introducing them in training. This dissertation developed a special training module aimed at developing the accuracy of foot strikes by improving the special physical training and technical-tactical training of students studying in the direction of sports activities (taekwondo WT) in higher educational institutions and developing their competitive potential. This module is used on the basis of a developed training plan and serves as an important factor in improving the quality of athletes ‘ training